Nature of chiral drugs and their occurrence in environment - Bhavtosh Sharma (MDPI AG, 2014)
Effectiveness of chiral drugs is very well established against several lethal diseases. The demand of chiral drugs is increasing day by day. Besides this, the racemization of some chiral drugs is also found in biological as well as in environmental matrices. The analysis of chiral drugs has become a necessary Research and Development Unit task for any analytical scientist, pharmaceutical institute or pharma industry considering not only the specific role of these drugs for better and suitable treatment of any lethal disease but also for their occurrence and fate in environmental matrices. The present article highlights the importance, bioactivities, occurrence and fate of chiral drugs in environment.